EXTENDED FINITE ELEMENT MODELLING (XFEM) OF INTERACTION BETWEEN HYDRAULIC FRACTURE AND NATURAL FRACTURE FOR UNCONVENTIONAL RESERVOIR - PRAKASAN, ARUVIN (2020)
The economical production of shale gas require well stimulation technique such as hydraulic fracturing. The hydraulic fracturing involves the injection of pressurized and high flow rate fluid into the formation to create the complex fracture network that consists of hydraulic fracture and natural fracture. The induced hydraulic fracture will be kept open by proppants during the flowback and the production. The success of hydraulic fracturing has increased the annual US dry gas production from 15 x 108 m3/D in 2000 to 24 x 108 m3/D in 2018. The hydraulic fracturing can be modeled by using numerical simulation, one of which is the Finite Element Method (FEM).